Critical points on egg production: causes, importance and incidence of eggshell breakage and defects - Helenice Mazzuco; Antonio Gilberto Bertechini (Ciência e Agrotecnologia, 2014)
The occurrence of broken eggs directly depends on the quality of the shell. It is important to consider that the problem of broken eggs is not due to a single factor but a combination of factors. Shell defects, irregularities in shell shape, texture and surface are commonly observed during a regular egg laying cycle and the causes are varied. The incidence of downgraded eggs still represents an important source of economic loss for the egg industry due to products damage and need for further processing. It is possible to obtain significant reduction in the number of eggs lost due to the inferior quality of the shell attempting to an adequate nutrition, disease control, good management practices, and use of genetic lines with higher quality eggshell traits.